Career opportunities with the discipline of public administration - Bansal, Meenakshi (2015)
Public administration can be defined both as an academic discipline and a field of practice. The times have changed and there is a considerable shift in the scope of public administration. It is primarily focused on the implementation of public policies and the people who execute these policies. With a specialisation in public administration, there are many career opportunities available to the students. For instance, graduates with a degree in public administration can make career in civil services or can work as an administrative officer, labour officer, corporate manager, consultant, management analyst, teacher, research associate, and in many other sectors. The present article provides an insight into the numerous career avenues available to the students of public administration.- Reproduced.
Keywords: Public administration